No enhancement of vestibular stimulation on visual working memory for actions - Luyao Hu; Zaifeng Gao; Qi Gao; Rui Wang (Scientific Reports)
Abstract Holding and processing actions in visual working memory (VWM) is crucial for daily functioning, but it is capacity-limited. The vestibular system, which is activated by both vestibular signals and visual gravitational motion, may be involved in this cognitive process. Past research indicates that galvanic vestibular stimulation (GVS) is a non-invasive technique that can enhance motor functions and various cognitive functions. However, the impact of GVS on VWM for actions has not been explored. This study addresses this gap by investigating whether GVS can improve VWM capacity for both upright and inverted actions. Using a virtual reality platform, we assessed VWM capacity in a change detection task, applying either STIM-current (0.8 mA) or SHAM-current (0 mA) GVS. The results showed no significant effect of GVS on VWM for either upright or inverted actions, at least for non-noisy GVS with stimulation intensity below cutaneous threshold. Despite the absence of significant effects, this study provides valuable insights into the interactions between the vestibular system and cognitive processes, laying the groundwork for future research on GVS applications in cognitive enhancement.